Effect of Dividend Policy on Stock Price Performance: Evidence from Nabil and Himalayan Banks - Dongol, Padam; Tandukar, Sikha (MVIC Journal of Management and Information Technology, 2025)
This study has examined impact of dividend policies on market price of share of commercial banks in Nepal. Out of 20 commercial banks in Nepal, two commercial banks namely Nabil and Himalayan bank limited have taken as sample. This research is based on secondary data collected during the period from 2014/15 to 2021/22. To achieve objective research descriptive and casual comparative research design have been used. It can be concluded that there is not any consistency in the dividend policy of the sample firms, therefore sometimes the result of the different tests accepts the theoretical assumptions of dividend policy and sometimes do not. It is found that majority of Nepalese firm gives priority to “earning” to get into the decision of dividend. The major conclusion of this study is that the earnings per share and dividend per share are positive and statistically significant factors that determine the market stock price, which means increase in earnings per share and dividend per share leads to the increase in market price of stock. Whereas dividend payout ratio has negative and significant relationship with market price per share. Likewise, dividend yield and earning yield ratios are negative statistically significant factors that determine the market price of stock providing enough evidence to accept the hypothesis. Finally, it can be concluded that dividend policy has significant relationship with the market price of stocks of commercial banks of Nepal and has impact on it.